Learning curve in the endovascular treatment of chronic post-thrombotic syndrome in a French center - Paul Segui; Valérie Monnin-Barès; Monira Nou; Sébastien Bommart; Hamid Zarqane; Juliette Vanoverschelde; Hélène Vernhet-Kovacsik (CVIR Endovascular)
Abstract Purpose Chronic post-thrombotic syndrome (PTS) is a frequent and disabling complication of deep vein thrombosis (DVT) with significant clinical impact. Endovascular stenting (EVS) has established itself as an effective technique but its availability remains limited to expert centers. We sought to identify the key determinants of our learning curve in EVS for PTS and the impact of this experience on our short and long-term results, in order to facilitate territorial dissemination and respond effectively to clinical demand. Material and methods We reviewed the records of 68 patients treated in our centre during eight years. We collected patients and disease characteristics, technical elements of the procedure, peri-procedural medical management and detail of the clinical follow-up and imaging. Results The median follow-up was 37 months. The primary, primary assisted and secondary patency rates were respectively 74%, 86% and 95%. A clinical benefit was observed in all patients from the start of our activity, without significant change whatever the operator experience. The main determinants of our learning curve were a progressive mastery of the procedure in its technicality and preparation, the evolution of the material and the improvement of the peri procedural management, allowing to reduce the duration of intervention, the rate of endovascular revision (38% to 4%, p < 0.01) but also the number of remote thrombotic events (29% to 6%). Conclusion EVS appears to be an effective therapeutic option in the management of PTS, with consistent clinical improvement observed even when performed by less experienced operators. Improvement in this technique comes with faster procedures, and a reduction of the occurrence of peri-procedural and long term thrombotic events. The implementation of this type of procedure requires multi-disciplinary collaboration with vascular medicine and corresponding angiologists.